Effect of Contour Furrows and Contour Bunds on Water Conservation in Grasslands of Western Rajasthan - Ullah, Wasi; Chakravarty, A K; Mathur, C P; Vangani, N S (Annals of Arid Zone, 2016)
Experimental plots were laid out in four centres at Jaisalmer, Bhopalgarh, Palsana and Jadan in western Rajasthan to study the effects of contour furrowing on soil moisture conservation and forage production from the rangelands. There were eight plots treated with contour furrows and contour bunds separately and in combination against One plot as control. The moisture percentage in the field (5-25 cm) attained a peak value by the end of July or in August depending upon the distribution of rainfall. The soil moisture depleted at varying rate till the end of October when it was mostly used for plant growth. Thereafter the loss was mainly due to evaporation. In Jaisalmer area soil moisture increase was comparatively higher in the treated plots and it was followed by Jadan and Bhopalgarh. This was due to shallow depths of soil in these areas. But in Palsana where depth of sandy soil was more, the infiltration rate was comparatively higher with consequent decrease in moisture at upper layers of the soil (5-25 cm). The contour furrowing and bunding treatments indicated increase in forage yield ranging from 14.1 per cent in Jadan to ]80.8 per cent in Jaisalmer areas during 1966 whereas the same treatment indicated increase in forage ranging from 4 4 to 37.4 per cent in 1967 in all the areas except Jaisalmer. This treatment also indicated comparatively bigher increase in moisture percentage in different areas. There was, however, variation in the yield of forage due to different treatments in different years indicating the need for similar investigation in other sets of conditions. The key forage and the perennial grass species, viz., Lasiurus sindicus. Cenchrus ciliaris, Cenchrus setigerus, and Eleusine compressa indicated increase in their percentage cover in the treated plots as compared to control, whereas Aristida and Oyperus spp. were adversely affected.